2010
DOI: 10.1021/jf1014268
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Echinacea angustifolia with Bauer Alkylamide 11 and Bauer Ketone 23 Increased Anti-inflammatory Potential through Interference with COX-2 Enzyme Activity

Abstract: Bauer alkylamide 11 and ketone 23 were partially responsible for Echinacea angustifolia anti-inflammatory properties previously. This study further tested their importance using the inhibition of prostaglandin E2 (PGE2) and nitric oxide (NO) production by RAW264.7 mouse macrophages in the absence and presence of lipopolysaccharide (LPS) and E. angustifolia extracts, phytochemical enriched fractions, or pure synthesized standards. Molecular targets were probed using microarray, qRT-PCR, western blot, and enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…paradoxa , which is also rich in Bauer ketones, could partly attribute its anti-inflammatory activity (inhibitory ability on NO, PGE2, IL-1β and IL-6 production) to Bauer ketones 23 and 24 (compounds 1, 2). Prior results from our laboratory (LaLone et al, 2009; LaLone et al, 2010) reported the inhibition of PGE2 and NO production by these ketones at concentrations found in E. pallida and E. Angustifolia , and the results in the present report with concentrations of Bauer ketones 23 and 24 (compounds 1, 2) that were found in E. paradoxa var. paradoxa were in agreement with the earlier results.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…paradoxa , which is also rich in Bauer ketones, could partly attribute its anti-inflammatory activity (inhibitory ability on NO, PGE2, IL-1β and IL-6 production) to Bauer ketones 23 and 24 (compounds 1, 2). Prior results from our laboratory (LaLone et al, 2009; LaLone et al, 2010) reported the inhibition of PGE2 and NO production by these ketones at concentrations found in E. pallida and E. Angustifolia , and the results in the present report with concentrations of Bauer ketones 23 and 24 (compounds 1, 2) that were found in E. paradoxa var. paradoxa were in agreement with the earlier results.…”
Section: Resultssupporting
confidence: 83%
“…The combined Bauer ketones were more effective than were individual Bauer ketones, with a 2-fold increase in COX-2 levels in relation to (Media+DMSO+LPS) control. LaLone et al (2010) reported that Bauer ketone 23 (compound 1) identified in an E. angustifolia extract had the capacity to increase COX-2 expression significantly at 5 μM in LPS-stimulated macrophages. In contrast, Bauer ketone 23 (compound 1) inhibited LPS-induced COX-2 activity at 0.83 μM (LaLone et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different components of Echinacea are likely responsible for suppressive or enhancing effects. Lalone et al found that combining an alkylamide with a ketene from E. angustifolia led to a greater anti-inflammatory effect on LPS induced PGE2 production suggesting that interaction of different constituents influences bioactivity [24]. Recent studies reported by Cech et al show that purified alkylamides from E. purpurea suppressed production of TNF-α and/or other cytokines and chemokines and PGE2 in RAW 264.7 macrophage cells infected with influenza A according to the concentration and structural type of the alkamides.…”
Section: Discussionmentioning
confidence: 99%
“…Generally ethanol extracts are expected to contain higher levels of alkylamides and phenolic compounds, while aqueous extracts contain more hydrophilic compounds such as polysaccharides and glycoproteins. Polysaccharides, glycoproteins, and cichoric acid have been identified as having immune-stimulating activity [11,20,21] in contrast to alkylamides and ketones that appear to be anti-inflammatory in vitro and in vivo [22-24]. Purified polysaccharide extracts from Echinacea increased macrophage chemotaxis, production of reactive oxygen intermediates (ROS), and inhibited growth of fungi in vivo [25].…”
Section: Introductionmentioning
confidence: 99%